Indonesian Muslim Youth and the Discourse on the Caliphate System, Islamic State and Sharia-Based Regional Regulations - Maghfur Ahmad (UIN K.H. Abdurrahman Wahid Pekalongan, 2021)
This study analyzes the discourse on the caliphate system, the Islamic state, and the Sharia-based regional regulation among Indonesian Muslim youth. After the reform era, the large flow of Islamic studies and political discourse in Indonesia was marked by a big wave of return of Islamic conservatism. The discourse of jihad, caliphs, Sharia-based regional regulation, and the struggle to bring about an Islamic state became lively. This study focuses on millennial young Islamic activists' responses whose join public schools in Pekalongan City, Central Java, Indonesia. With a qualitative approach, this study's data were obtained through interviews, observation, and documentation. The data were analyzed through an interactive analysis tool introduced by Miles and Huberman. The results of this study reveal that Muslim youths have multiple personalities. They want to be entirely religious and apply Islam in all aspects. Still, they are also aware that a state based on Pancasila (Five principles) is the right choice in a pluralistic Indonesian context. This study also found that the majority of Indonesian youths had minimal literacy in the constituent debate on religious and state relations during the formation of the Indonesian state. This fact impacts the lack of awareness, understanding, and contextualization of the caliphate system's discourse, the Islamic state, and the Sharia regulation among Indonesian Muslim youth. On the other hand, the strengthening of textual understanding and the lack of awareness of nationalism literacy are the threat to the sustainability of the Indonesian nation’s future.